Numerical modeling of meter-size solid dynamics in high density solitary areas of a massive circumstellar disc - Stoyanovskaya, O.P.; Snytnikov, V.N. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
The planetary system formation can proceed via the development of global gravitational instability in a massive circumstellar disc. At this stage, the disc can be considered as a multi-phase medium of gas and primary solids mainly of meter in size. Large solitary vortices of high gaseous density can be formed in such a disc. It is shown that the numerical model based on SPH and PIC methods allows one to study the dynamics of solids in gaseous vortices forming in the disc, including the regimes when the concentration of solids is locally increased. The influence of numerical resolution on the solids thermalization time reproduced in the model is estimated.